(3cJGH aj GdJGQjNs
(3ChdgG (B:s
(3GHf Ydj Hf YHOGdQMef Hf YHOGdUGOb Hf YHOGdQMef GdSHWj Hf aGWeI HfJ QShd Gdg Udi Gdg Ydjg hSde s
(3BNQgG (B:s
(3hcGf GdaQGZ efg UHjMI GdNejS ef TgQ Gdg GdoeYXe QeVGf HYO eGeVJ efg CQHYI hYTQhf jhke YGe (B1200 (3eGFJjf hCda Ydi jO SjOj eMeO GHf YHOGddg Hf ehSi s
(3hgh aj PcQ ef jfJgj fSHg Edi GdSjOI aGWeI GdRgQGA QVj Gddg YfgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B337 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdJGQjNs